Apes in a changing world - the effects of global warming on the behaviour and distribution of African apes - Lehmann, J; Korstjens, A; Dunbar, R (2010)
Aim In this study we use a modelling approach to identify: (1) the factors responsible for the differences in ape biogeography, (2) the effects that global warming might have on distribution patterns of African apes, (3) the underlying mechanisms for these effects, and (4) the implications that behavioural flexibility might be expected to have for ape survival. All African apes are highly endangered, and the need for efficient conservation methods is a top priority. The expected changes in world climate are likely to further exacerbate the difficulties they face. Our study aims to further understand the mechanisms that link climatic conditions to the behaviour and biogeography of ape species.Location Africa.Method We use an existing validated time budgets model, derived from data on 20 natural populations of gorillas (Gorilla beringei and Gorilla gorilla) and chimpanzees (Pan troglodytes and Pan paniscus), which specifies the relationship between climate, group size, body weight and time available for various activities, to predict ape distribution across Africa under a uniform worst-case climate change scenario.Results We demonstrate that a worst-case global warming scenario is likely to alter the delicate balance between different time budget components. Our model points to the importance of annual temperature variation, which was found to have the strongest impact on ape biogeography. Our simulation indicates that rising temperatures and changes in rainfall patterns are likely to have strong effects on ape survival and distribution, particularly for gorillas. Even if they behaved with maximum flexibility, gorillas may not be able to survive in most of their present habitats if the climate was to undergo extreme changes. The survival of chimpanzees was found to be strongly dependent on the minimum viable group size required.Main conclusions Our model allows us to explore how climatic conditions, individual behaviour and morphological traits may interact to limit the biogeographical distributions of these species, thereby allowing us to predict the effects of climate change on African ape distributions under different climate change regimes. The model suggests that climate variability (i.e. seasonality) plays a more important role than the absolute magnitude of the change, but these data are not normally provided by climate models. © 2010 Blackwell Publishing Ltd.